Association between polymorphisms of the E-selectin gene, hepatitis B virus DNA copies and preS1 antigen in patients with chronic hepatitis B infection - CAI, WEI JUAN; YIN, LIANG; ZHOU, DI; CAO, WEN JIANG; ZHENG, WEI WEI; SHENG, LEI; CHENG, JIANG (Molecular medicine reports, 2012)
The aim of this study was to investigate the relationship between E-selectin +G98T, +A561C polymorphisms and the levels of hepatitis B virus (HBV) DNA and preS1 antigen (preS1Ag) in patients with chronic hepatitis B (CHB) infection. Polymorphisms of the E-selectin gene in 150 CHB patients and 150 healthy controls of two different nationalities were detected using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Real-time quantitative PCR was used to detect the levels of HBV DNA. preS1Ag and five items of hepatitis B were detected by enzyme-linked immunosorbent assay. Two genotypes, GG (94%, 96%) and GT (6%, 4%) of the E-selectin +G98T polymorphism, and AA (78.67%, 80.67%) and AC (21.33%, 19.33%) of the +A561C polymorphism, were found in these patients. There were also significant differences in the two nationalities in the genotypic frequencies in +A561C polymorphisms between patients and healthy subjects (χ2=5.489, χ2=5.653; P<0.05). In the patients studied, the relative risk of suffering from CHB in genotype AC was 2.122 and 2.313-fold higher for the two nationalities, respectively, than that of the AA genotype (OR=2.122, 95% CI 1.121-4.019; OR=2.313, 95% CI 1.002-5.360). There was also significant over-representation in the C allele frequency between the two groups (χ2=5.000, χ2=5.30; P<0.05), and the levels of HBV DNA and preS1Ag in the AC genotype patients were higher than those in the AA genotype (P<0.01 and P<0.05). E-selectin +A561C and +G98T polymorphisms were present in the populations studied. Therefore, there is a correlation between E-selectin +A561C polymorphisms and CHB. Allele C may be one of the predisposing factors, and mutation of this locus may impact the virus copy number.